Beta-lactam allergy labeling in intensive care units: An observational, retrospective study. Issue 27 (9th July 2021) - Leone, Marc; Zunino, Claire; Pauly, Vanessa; Mathieu, Calypso; Antonini, François; Orlean, Veronica; Cassir, Nadim; Pradel, Vincent; Bourenne, Jérémy; Boussen, Salah; Hraiech, Sami; Lagier, David; et al.
Abstract : Abstract: This retrospective study aimed to describe the association between the "β-lactam allergy" labeling (BLAL) and the outcomes of a cohort of intensive care unit (ICU) patients. Retrospective cohort study. Seven ICU of the Aix Marseille University Hospitals from Marseille in France. We collected the uses of the label "β-lactam allergy" in the electronic medical files of patients aged 18 years or more who required more than 48 hours in the ICU with mechanical ventilation and/or vasopressors admitted to 7 ICUs of a single institution. We retrospectively compared the patients with this labeling (BLAL group) with those without this labeling (control group). The primary outcome was the duration of ICU stay. Among the 7146 patients included in the analysis, 440 and 6706 patients were classified in the BLAL group and the control group, respectively. The prevalence of BLAL was 6.2%. In univariate and multivariate analyses, BLAL was weakly or not associated with the duration of ICU and hospital stays (respectively, 6 [3–14] vs 6 [3–14] days, standardized beta −0.09, P = .046; and 18 [10–29] vs 15 [8–28] days, standardized beta −0.09, P = .344). In multivariate analysis, the ICU and 28-day mortality rates were both lower in the BLAL group than in the control group (aOR 0.79 95% CI [0.64–0.98] P = .032 and 0.79 [0.63–0.99] P = .042). Antibiotic use differed between the 2 groups, but the outcomes were similar in the subgroups of septic patients in the BLAL group and the control group. In our cohort, the labeling of a β-lactam allergy was not associated with prolonged ICU and hospital stays. An association was found between the labeling of a β-lactam allergy and lower ICU and 28-day mortality rates. Trial registration: Retrospectively registered.